2017
DOI: 10.1111/cfs.12420
|View full text |Cite
|
Sign up to set email alerts
|

Foster care placement breakdown in the Netherlands and Flanders: Prevalence, precursors, and associated factors

Abstract: Family foster care is the option of choice for children in need of out‐of‐home care in Flanders and the Netherlands. Foster care is however a vulnerable intervention, and questions can be raised as to its efficacy. Although the literature on placement breakdown has made significant progress during the last years, empirical knowledge regarding breakdown in Flanders and the Netherlands remains scant. Consequently, this study aimed at investigating prevalence and precursors of breakdowns in long‐term foster care,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
3
15
0
2
Order By: Relevance
“…Although there was large variation, foster children resided on average >4.5 years with their current foster family which might indicate that they are stably settled in their foster families. In line with previous studies ( Oosterman, Schuengel, Slot, Bullens, & Doreleijers, 2007 ), a recent retrospective study examined both foster children’s behaviour problems on admission and after 6 months in relation to breakdown and found that only behaviour problems on admission were significantly associated with breakdown ( Vanderfaeillie, Goemans, Damen, Pijnenburg, & Van Holen, n.d. ). It would be of interest to examine whether the risk of breakdown, which is most prevalent during the first months of the placement, can be predicted in a longitudinal study using a screening measure such as the BAC.…”
Section: Discussionsupporting
confidence: 76%
“…Although there was large variation, foster children resided on average >4.5 years with their current foster family which might indicate that they are stably settled in their foster families. In line with previous studies ( Oosterman, Schuengel, Slot, Bullens, & Doreleijers, 2007 ), a recent retrospective study examined both foster children’s behaviour problems on admission and after 6 months in relation to breakdown and found that only behaviour problems on admission were significantly associated with breakdown ( Vanderfaeillie, Goemans, Damen, Pijnenburg, & Van Holen, n.d. ). It would be of interest to examine whether the risk of breakdown, which is most prevalent during the first months of the placement, can be predicted in a longitudinal study using a screening measure such as the BAC.…”
Section: Discussionsupporting
confidence: 76%
“…The likelihood that foster and adoptive families already received extra support, for example, a parenting intervention to improve parenting skills, is also greater when the duration of the placement is longer. As stated before, there is evidence that the risk of placement disruption is smaller when caregiving quality is good and when the placement lasts longer (Oosterman et al, 2007; Vanderfaeillie et al, 2017). In addition, if the duration of the placement is longer, it is more likely that the children where younger at time of placement.…”
Section: Discussionmentioning
confidence: 92%
“…This information suggested that the variation in placement duration is large, but the possible moderating role of placement duration could not be examined. Moreover, longitudinal effectiveness studies of parenting interventions on placement disruption are needed, because (foster care) research shows that the first 18 months after placement may be critical for placement disruption (Vanderfaeillie, Goemans, Damen, Van Holen, & Pijnenburg, 2017). The existing intervention studies often were too short or provided incomplete data on placement duration to draw conclusions about the effects on placement disruption.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found that the chance of breakdown is highest in the months following the placement, e.g. : highest chance during the first 18 months according to the study by Vanderfaeillie, Goemans, Damen, Van Holen, and Pijnenburg (2018) and during the first 6 months according to the study by Wulczyn, Kogan, and Harden (2003). Within our study, at the moment of assessment with the SDQ only 22% of the foster children were with the foster family for less than 18 months.…”
Section: Discussionmentioning
confidence: 48%